The Columba-Hypatia Project: Astronomy for Peace. Issue Volume 14:Issue A30(2018) (August 2018) - Fragkoudi, Francesca
Abstract: "Columba-Hypatia: Astronomy for Peace" is a joint astronomy outreach project by GalileoMobile and the Association for Historical Dialogue and Research (AHDR) which takes place on the divided island of Cyprus. The project aims to inspire young people, through astronomy, to be curious about science and the cosmos, while also using astronomy as a tool for promoting meaningful communication and a Culture of Peace and Non-violence. We conduct educational astronomy activities and explore the cosmos with children and the public, bringing together individuals from the various communities of Cyprus 'under the same sky' to look beyond borders and inspire a sense of global citizenship.